Correlation between Pelvic Diameter and Different Surgical Procedures for Exogenous Cervical Leiomyoma - Lifang Xue; Liying Wang; Xu Mu; Xiaoyan Xie; Kaiwu Lin; Liangzhi Cai (Wolters Kluwer Medknow Publications, 2024)
Objectives: The objective of the study was to investigate the clinical value of pelvic diameter in the evaluation of surgical difficulty and selection of the best surgical plan for exogenous cervical leiomyomas. Materials and Methods: Sixty-five patients with exogenous cervical leiomyomas admitted to our hospital from 2012 to 2021 were enrolled. All patients underwent pelvic magnetic resonance imaging examination before surgery and received surgical treatment within 1 week. Relevant clinical data were collected. According to the surgical approach, they were divided into two groups: the laparoscopic group and the laparotomy group. The clinical significance of the pelvic diameter line in the surgical selection of exogenous cervical leiomyomas was discussed by retrospective analysis of the correlation between the pelvic diameter line and the collected clinical indicators. Results: There was no significant difference in tumor location and pelvic diameter between the two groups (P > 0.05). However, there was a significant difference in tumor diameter and the ratio of tumor diameter line to pelvic diameter line (P < 0.05). In addition, the laparoscopic group underwent more myomectomy than hysterectomy and lost more blood during operation (P < 0.05).The postoperative index showed that patients in the laparotomy group had a higher proportion of full of cellular leiomyoma, higher postoperative temperature, and longer postoperative exhaust time (P < 0.05). Conclusion: The ratio of the tumor diameter line to the pelvic diameter line is correlated with the surgical plan selection of exogenous cervical leiomyomas, which may be used to evaluate the surgical difficulty of these patients and the selection of the suitable surgical plan.